SIMBOL DAN MAKNA TARI PERANG CENTONG DALAM TRADISI NGASA KAMPUNG BUDAYA JALAWASTU SEBAGAI PELESTARIAN BUDAYA - Turyati Turyati; Viola Vianda Sari; Septiana Yustika Widyaningrum (PANGGUNG, 2026)
This study examines Tari Perang Centong in the Kampung Adat Jalawastu community, Brebes, specifically its role during the Tradisi Ngasa ceremony. Beyond performance, the dance acts as a cultural representation of community ideology. This study aims to analyze the symbols in Tari Perang Centong and their role in preserving ancestral culture. Employing a qualitative ethnographic approach, the research utilized participant observation, in-depth interviews, and documentation to collect data. Applying Roland Barthes’ semiotic theory, the findings reveal that the dance’s choreographic symbols manifest the community’s local life, belief systems, and cultural identity. Tari Perang Centong serves as a vital medium for transmitting cultural values across generations, thereby strengthening communal identity and preserving ancestral traditions. Ultimately, this research contributes to the academic study of performing arts and provides a strategic reference for cultural preservation efforts.